The Effect of Problem Based Learning with Gallery Project and Locus of Control on Learning Achievement - Vicky Pratica Evita Sari; Amat Mukhadis (Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
The purpose of this study was to examine the significance of difference in achievement between the students taught using the Problem Based Learning with Gallery Project and the Expository Learning as well as those having an internal and external locus of control, along with its interaction. This quasi-experimental study involved 52 students, randomly sampled. The methods of data collection were observation, non-test, and test. The method of analysis was a two-way ANOVA. The result of this study indicated that: (1) there was a significant difference in achievement between students taught using the PBL with Gallery Project and those taught using the Expository Learning; (2) there was no significant difference between students having an internal locus of control and those having an external locus of control on basic work of automotive engineering in a vocational high school; and (3) there was no interaction between the PBL with Gallery Project and locus of control level toward student achievement.